Coffee cherry’s pulp variety and pulping delay time leading to cascara tea products - Oktaviani, S.; Yuwana, Y.; Hidayat, L. (International Journal of Agricultural Technology, 2021)
The effect cherry’s pulp variety and pulping delay time after harvest on the physical, chemical, and organoleptic properties of cascara tea products were investigated. The results indicated that all parameters were decreased with the pulpingdelay times, excepts the ash content.The best robusta cascara tea was characterized by 4.90% of yield, 6% of moisture content, the lightest color value 7.5 YR 7/8, 4.01 of pH, 7% of ash content, 241.19 mg/L of polyphenol content, 554.74 mg/ L of tannin content, 32.67 ppm of antioxidant activity and 107.03 mg/L of caffeine content. On the other hand the best arabica cascara tea demonstrated 7.74% of yield, 6.67% of moisture content, the strongest color intensity 5 YR 5/10, 4.33 of pH, 5.33% of ash content, 170.87 mg/L of polyphenol content, 334.91 mg/L of tannin content, 12.80 ppm of antioxidant activity and 56.08 mg/L of caffeine content. The robusta cascara tea excelled in in the moisture content, polyphenol content, and tannin content while the Arabica cascara tea was superior in yield, pH, ash content, antioxidant activity, and caffeine content. In term of organoleptic scores the Arabica cascara tea produced from the fresh pulp was the most preferable for the panelists. All pulps were qualified as raw material for cascara tea production